2013
DOI: 10.1007/s12663-012-0446-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Pattern of Cranio-Maxillofacial Injuries: A 22 year Retrospective Analysis of Cases Operated at Major Trauma Hospitals/Centres in Pune, India

Abstract: This study aims to retrospectively analyze the incidence and pattern of cranio-maxillofacial injuries in the developing world in a hope to emphasize on authorities the need of improvising infrastructural facilities, medical and other. Hospital medical records with available radiographs of 6,872 patients treated for cranio-maxillofacial injuries at major trauma centres in Pune, India over a 22 year period (from July 1989 to June 2010) were reviewed. Relevant data pertaining to patients' age, sex, cause of injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
4
21
0
Order By: Relevance
“…But some western studies have also recognized assault as the leading cause [17,18]. In the present study RTA was the single highest contributing factor, similar to various studies conducted in various states of India [6,8,9,16,19]. In the studies from developed countries like Greece [20], New Zealand [21], United Kingdom [22] RTA as the causative factor was found to be low.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…But some western studies have also recognized assault as the leading cause [17,18]. In the present study RTA was the single highest contributing factor, similar to various studies conducted in various states of India [6,8,9,16,19]. In the studies from developed countries like Greece [20], New Zealand [21], United Kingdom [22] RTA as the causative factor was found to be low.…”
Section: Discussionsupporting
confidence: 84%
“…Most of the studies have attributed RTA as accounting for maximum maxillofacial injuries [6,14,16]. But some western studies have also recognized assault as the leading cause [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Associated injuries were found in 28.9% of patients with maxillofacial fracture (368 of 1,275 cases) and comprised head injury in 58% of patients, thoracic injury in 24%, abdominal injury in 8%, pelvic injury in 6%, and C-spine injury in 4%, as shown in Figure 2, corresponding to the studies of Chalya et al [3] and Gadre et al [4] who found that head injuries occurred in 53.1% and 56% of patients with maxillofacial trauma, respectively. Head injuries are the most commonly associated injuries because the forces that can cause facial bone fractures might also cause brain injuries.…”
Section: Associated Injuriessupporting
confidence: 61%
“…These results show that men are at a higher risk of maxillofacial injuries than women. [3][4][5][6] and in contrast with the study of Boonkasem et al [2] that found that the number of patients in each age group was not different (~19%). However, the study by Boonkasem et al included only 210 patients and was conducted in a rural area, whereas our study was conducted in a trauma center in an urban area.…”
Section: Discussionmentioning
confidence: 93%
“…However, assaults are not the only mechanism causing isolated maxillofacial injuries. In fact, many other studies reported that assaults ranked after road traffic accident [8].…”
Section: Epidemiology Of Intentional Isolated Maxillofacial Traumamentioning
confidence: 99%